Implications of the Uruguay Round for Kenya - Chandha, Rupa (IMF Working Papers; Working Paper ;, 1996)
This paper studies the implications of the Uruguay Round for Kenya's own trade regime and its external trading environment. The analysis indicates that Kenya did not undertake significant liberalization commitments under the Uruguay Round. There are however, several effects on Kenya's external trading environment due to most-favored nation tariff cuts, erosion of preference margins, and changes in food prices. These effects are determined using simple computational techniques in a partial equilibrium framework. Overall, the results indicate that the effect on Kenya's balance of payments in the medium-term may be negative but modest, and can be offset by pursuit of appropriate structural adjustment policies.